Factors Behind The Attainment of Going Concern Audit Opinion: A Study on Indonesian Capital Market From Period 2005 to 2013 - Bayu Wiratama; Ali Djamhuri (Jurnal Ilmiah Mahasiswa FEB, 2014)
The aim of this descriptive quantitative study are to find out the relationship in CPA firm’s reputation, prior year audit opinion, and company’s growth towards the attainment of going concern audit opinion. There were 31 manufacture companies listed in BEI for period 2005-2013 used as sample for this  minor  thesis.  Purposive  sampling  method  used  to  determine  those  samples.  The  logistic regression test result shows that prior year audit opinion has a positive effect on the attainment of going concern audit opinion. Meanwhile, CPA firm’s reputation and company’s growth has no effect on the attainment of going concern audit opinion.   Key Words: going concern audit opinion, CPA firm’s reputation, prior year audit opinion, company’s growth, logistic regression.